O socialismo indígena de Mariátegui - Mesquita, Afonso Mancuso de [UNESP]; Adoue, Silvia Beatriz [UNESP] (My University, 2012)
The theme of indigenism in Mariátegui’s thinking can only be understood as indigenous socialism. His original interpretation of Peruvian reality reveals a double heterodoxy, both from the standpoint of current indigenism and the socialist theory of his time. The first one defends exclusively the autochthon elements to face the imperialist power. The second one didn’t recognize the Latin American particularities to define the revolutionary duties. When Mariátegui states that the Peruvian socialism should be based on the remaining forms of indigenous agrarian communitarianism, he overcomes both (current indigenism and socialist theory) and offers a dialectical synthesis, condensed in a single proposition: Indigenous-American Socialism.

O indigenismo em Mariátegui só pode ser compreendido como socialismo indígena. Sua interpretação original da realidade peruana nos revela uma dupla heterodoxia, tanto do ponto de vista do indigenismo quanto da teoria socialista correntes em sua época. O primeiro defendia exclusivamente os elementos autóctones contra o poder imperialista e a segunda não reconhecia as particularidades latino-americanas na definição das tarefas revolucionárias Mariátegui, ao afirmar que o socialismo no Peru deveria ter como base as formas remanescentes de comunitarismo agrário indígena, supera ambas correntes e propõe uma síntese dialética ao pensar o socialismo peruano, condensada na proposição socialismo indo-americano.
Keywords: Indigenism; José Carlos Mariátegui; Marxism; Latin-America; Unequal and combined development; Indigenismo; José Carlos Mariátegui; Marxismo; América Latina; Desenvolvimento desigual e combinado